Moving Chipless RFID Tag Detection Using Adaptive Wavelet-Based Detection Algorithm - Bibile, Meriam Anushani; Karmakar, Nemai Chandra (IEEE transactions on antennas and propagation, 2018)
The detection of a chipless radio frequency identification (RFID) tag in stepped motion is proposed. The performance is evaluated through experiment and measured using the vector network analyzer. The postprocessing of the measured results is performed using MATLAB. A novel adaptive wavelet-based detection algorithm is used for the decoding of the tag ID. An error analysis is conducted on the experimental results to study the variation of magnitude and frequency due to the movement of a chipless RFID tag. As far as the tag signature has not been disappeared from the reading range it has the same confidence level for the detection of its tag ID. This opens a new avenue toward developing the detection algorithms and decoding techniques when the chipless RFID tag is in motion. It also opens the doors for the localization of moving chipless RFID tags and prediction of the tagged objects moving trajectory modeling in the future.